Library Advocacy: Ecosystem Concepts Can Provide a Strong Foundation for Library Advocacy - Wood, Jennifer (Maine Policy Review, 2024)
This commentary provides a definition of library ecosystem and describes how ecosystem work can positively affect library or association advocacy by helping groups speak with one voice. When libraries work together, across library types and with other invested stakeholders, and speak with one voice, advocacy messages are stronger.